1999
DOI: 10.1161/01.cir.99.18.2452
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Sudden Cardiac Death by Dietary Pure ω-3 Polyunsaturated Fatty Acids in Dogs

Abstract: These results indicate that purified omega-3 fatty acids can prevent ischemia-induced ventricular fibrillation in this dog model of sudden cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
231
5
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(253 citation statements)
references
References 28 publications
10
231
5
7
Order By: Relevance
“…Some studies have observed a beneficial impact of n-3 PUFAs on the prevention of ventricular arrhythmias in dogs (37), rats (38,39) and nonhuman primates (40). Regarding in vitro studies, Kang and Leaf observed that addition of low micromolar concentrations of EPA or DHA slowed the beating rate of the myocytes (41).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have observed a beneficial impact of n-3 PUFAs on the prevention of ventricular arrhythmias in dogs (37), rats (38,39) and nonhuman primates (40). Regarding in vitro studies, Kang and Leaf observed that addition of low micromolar concentrations of EPA or DHA slowed the beating rate of the myocytes (41).…”
Section: Discussionmentioning
confidence: 99%
“…Original observations in experimental myocardial infarction 11 and later studies by McLennan et al [12][13][14] in rats and monkeys suggested that omega-3 FAs had a direct protective effect on the heart itself. In a dog model of ventricular tachyarrhythmia, 15 infused omega-3 FAs reduced the number of potentially fatal arrhythmias. Investigations using isolated cardiac myocytes revealed that EPA and DHA could prolong the refractory state of these cells by interaction with fast-acting sodium channels and L-type calcium channels.…”
mentioning
confidence: 99%
“…Rats chronically fed a diet high in n-3 PUFA were significantly less likely to have ventricular fibrillation during acute myocardial ischemia than were animals fed a control diet [7]. Similarly, the acute infusion of n-3 PUFA in a dog model of acute ischemic ventricular fibrillation was associated with a marked reduction in the risk of the arrhythmia [8]. The Physician's Health study showed a reduction in sudden death with higher fish intake but no reduction in the risk of myocardial infarction [9].…”
Section: Meritt H Raittmentioning
confidence: 93%